Data Analytics for Enhancing the Efficiency of Digital Public Services - Ardyansyah, Nadia Paramitha; Waluyo, Rizky Adimas (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2026)
Digital transformation encourages governments to enhance data-driven services, but digitalization alone cannot ensure fast, accurate processes without adequate analytical capabilities. This study examines how data analytics capacity influences the efficiency of digital public services, focusing on response speed, service-flow accuracy, and operational stability. Using an explanatory sequential mixed-methods design, the research analyzes 200-300 digital service transactions collected over 3-6 months through descriptive statistics and regression, followed by semi-structured interviews with 6-10 data analysts, application managers, and service personnel to deepen the quantitative insights. Results show that applying data analytics accelerates response time by up to 31 percent, reduces error rates to below 2 percent, and maintains stable turnaround times even during peak demand. Analytics also helps agencies identify operational patterns and strengthens evidence-based decision-making, supporting the development of an empirical model that links analytics capability to digital service efficiency, an area rarely assessed within Indonesian public administration. The study highlights practical implications, including the need to improve real-time dashboards, automate monitoring tools, and enhance staff data literacy to accelerate digital reform and deliver more responsive, accurate, and reliable public services.